MIKROHABITAT KATAK TANPA PARU-PARU (Barbourula kalimantanensis Iskandar, 1978) DI KAWASAN TAMAN NASIONAL BUKIT BAKA BUKIT RAYA KABUPATEN MELAWI KALIMANTAN BARAT - Maisyara, Sitti (Universitas Tanjungpura, 2019)
Barbourula kalimantanensis is the only frog in Indonesian that has no lungs and only founded in Kalimantan. This study aims to study microhabitat of the lungless frog at Resot Belaban in Bukit Baka Bukit Raya National Park. The method of data collection was done by using Visual Encounter Survey (VES) combining with of tracking systems. The data are taken in 4 observations stations: Ella river 0, Ella river 1, Ella river 2, and Belaban river with tree time repeatly in each station. Based on the result, B.kalimantanensis was found only one specimen in Ella river. The microhabitat of Barbourula kalimantanensis consisted of range air temperature 25˚c – 30˚C, humidity 73% - 95%, water temperature at night ranges from 13º - 14ºC and in the noon 16˚c with a water pH approaching 6.50. The intensity of light entering a location with a large enough amount 125.4 Cd. Dissolved oxygen 7.10 with dissolved solids 7.53 and non-dissolved solids 9. Analysis of water from the four rivers shows that the water in Ella river 0 and Belaban river have pH of water is close to netral pH (7), normal water temperature (27ºC), and the content of dissolved solids and undissolved solids in it. These indicate that the water from both rivers is suitable for humn consumption. The small fish and insect larvae who lived in the river are become a potential prey for B. kalimantanensis. Keywords : Barbourula kalimantanensis, Frog, Herpetofauna, Microhabitat, TNBBBR